The Effect Of Higher-Order Thinking Skill In Reading Comprehension - Lauren Hotmauli Silalahi; Maria Melati Sitorus; Hana Rajagukguk; Netti Panggabean; Jamaluddin Nasution (Institut Agama Islam Negeri Palopo, 2021)
AbstractThis study aimed to find out rather higher-order thinking helped Junior High school students develop their reading comprehension or not. The research design that used in this research was quantitative and qualitative. The treatment group consists of 30 students, and the group of control also consists of 30 students. In response to an international educational problem, the Indonesian government has created a higher education system. To participate in global competitions in the twenty-first century, Students in Indonesian must think critically and creatively. Several research studies find how teachers use HOTS in many ways. The skill is integrated into the curriculum and application methods by the teacher. The study uses a T-test and interview to find out the effect of HOTS (higher-order thinking skill). The study was conducted at SMP NEGERI 7 in Medan. The test of the research instrument was split up into two parts: Pre-test and post-test, and variability of statistical measured based on the post-test result for two groups in terms of significance.